Determination of crop coefficients, water requirements and water productivity for maize (Zea mays L.) under central Gezira clay soil conditions, Sudan - Mohammed, Hisham M.; Adam, Hussien, S.; Idris, Siddig. E.; Muhieldeen, Osama A. (Gezira Journal of Agricultural Science, 2016)
Development of site specific crop coefficients (K c ) helps tremendously in irrigation management and furthermore provides precise water application in the region. This study was conducted at the Experimental Farm, University of Gezira, during seasons 2014/15 (first season) and 2015/16 (second season) to estimate crop coefficients (K c ), crop water requirements (CWR) and water productivity (WP) of maize cultivar Hudaiba2. The reference evapotranspiration (ET o ) was calculated using the FAO computer program (CROPWAT). Actual crop evapotranspiration (ET c ) was estimated by the gravimetric method. Crop coefficients were derived from the relationship between reference evapotranspiration and actual crop evapotranspiration.  The results showed that crop coefficients values for maize were 0.51 and 0.47 for initial stages, 1.26, and 1.15 for the mid stages and then decreased gradually to 0.53 and 0.42 for the late stages, in the first and second season; respectively. The peak K c occurred during the period 60 to 70 days after sowing (DAS), coinciding with the maximum ET c of 6.75 mm/day at the mid-season stage for maize. The crop consumptive water use of maize were 491 mm (4910 m 3 /ha) for the total growing period. The mean yield of maize was 4285kg/ha and the crop water productivity was 0.58 kg/m 3 .